The Effects of User Intention and User Satisfaction on E-Filling Adoption in Indonesia: A Systematic Literature Review - Lestari, Rahayu; Digdowiseiso, Kumba (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Intention, as the main indicator of an individual's desire to adopt a technology, influences the extent to which they are willing to use and invest in e-filling. The aim of this research is to find out how ser intention (user intention) has a significant effect on the level of e-filling adoption in Indonesia, and what factors motivate individuals to have high user intention towards technology. The structure of this research literature review reflects the systematic approach applied in conducting a literature review to support understanding the impact of User Intention and User Satisfaction on the adoption of E-Filling in Indonesia. The results of this research are that a holistic strategy that includes good interface design, support for social norms, increasing digital literacy, and meeting user expectations through security and efficiency is the key to achieving successful e-filling adoption in Indonesia.